GAME ONLINE DAN AKTIVITAS FISIK MEMPENGARUHI KUALITAS TIDUR PADA REMAJA - Adyani, Sang Ayu Made (Indonesian Journal of Health Development, 2025)
Online gaming addiction is the excessive act of playing games over the internet. Too much online gaming and sedentary activities increase the risk of developing diseases. Increasing activity is one way to reduce the likelihood of developing diseases, online game addiction can have a negative impact on health because it affects sleep. This study aims to analyze the relationship of online gaming and physical activity with sleep quality in adolescents. The method used in this study was cross-sectional with data collection through google form. A total of 300 participating respondents were selected through stratified random sampling technique. The results of this study indicate that there is a significant relationship between online gaming, physical activity, and sleep quality in adolescents. Researchers suggest that adolescents should pay attention to time limits for playing online games, and not forget the main tasks of adolescents by doing other activities that are more useful, and must be able or able to control to consume caffeine, not constantly dependent on nicotine, and avoid narcotics, Adolescents should also better understand and realize the adverse effects caused by poor adolescent sleep quality.